2014
DOI: 10.4103/0253-7184.132404
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in congenital syphilis

Abstract: In many parts of the world particularly sub-Saharan Africa, congenital syphilis is a significant public health problem. Though it is rare in most affluent countries there has been a slight resurgence recently in several European countries. The diagnosis of suspected cases and management of congenital syphilis may be confusing and the potential for severe disability is high when cases are missed. The cornerstone of congenital syphilis control is antenatal screening and treatment of mothers with penicillin and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 4 publications
0
19
0
6
Order By: Relevance
“…Immigrant mothers may have a low socioeconomic background and may not have access to prenatal care, thus, increasing incidence of CS in immigrant mothers could be related to failure of prenatal care delivery systems (91617). A rising trend in the incidence of syphilis and CS has also been observed in other Asian and Western countries (12181920). A sharp increase in the incidence of syphilis infection has been documented among heterosexual population and men who have sex with men.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Immigrant mothers may have a low socioeconomic background and may not have access to prenatal care, thus, increasing incidence of CS in immigrant mothers could be related to failure of prenatal care delivery systems (91617). A rising trend in the incidence of syphilis and CS has also been observed in other Asian and Western countries (12181920). A sharp increase in the incidence of syphilis infection has been documented among heterosexual population and men who have sex with men.…”
Section: Discussionmentioning
confidence: 55%
“…Since the initiation of national programs to prevent CS, it was considered a disease of the past in developed countries. Despite the marked advances in the management and control of syphilis, the incidence of syphilis is increasing again in many parts of the world (1238). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital syphilis is an infection that has demonstrated resurgence in many developed countries, including the United States. Based on estimates by the World Health Organization, the annual incidence of congenital syphilis worldwide has been reported to be as high as 1 575 000 cases . Recent trends have showed that the overall rate of reported congenital syphilis in the United States has increased from 8.4 cases per 100 000 live births in 2008 to 2012 to 11.6 in 2014—the highest congenital syphilis rate reported since 2001 .…”
Section: Discussionmentioning
confidence: 99%
“…Syphilis in pregnant women is transmitted to the fetus via transplacental passage, and has an infection rate of 25-75% [4]. Paradoxically, the fetal consequences of transplacental transmission of syphilis exhibit an inverse relationship with the length of maternal infection.…”
Section: Congenital Syphilismentioning
confidence: 99%